(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The spleen is a peripheral organ of the immune system, involved in hematopoiesis and is a cemetery for old red blood cells. A brief review presents the latest literature data on the structural and functional areas and cellular components of the organ and the functions they perform.